2020
DOI: 10.1080/23802359.2020.1721373
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genome of a medicinal species Polygonatum kingianum in China (Asparagaceae, Asparagales)

Abstract: 2020) Complete chloroplast genome of a medicinal species Polygonatum kingianum in China (Asparagaceae, Asparagales), Mitochondrial DNA Part B, 5:1, 959-960, ABSTRACTPolygonatum kingianum is a medicinal and food plant distributed in most of countries throughout the temperate Northern Hemisphere. Here we report on the complete chloroplast (cp) genome sequence of P. kingianum. The cp genome is 155,399 bp in size and includes two inverted repeat regions of 52,7411 bp, which is separated by a large single-copy regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…So, in the present study, we constructed a maximum-likelihood phylogenetic tree based on concatenated 75 protein-coding genes of 19 Nolinoideae species and revealed that all the species formed a monophyletic group and S. gardenii formed a cluster with R. carnea, R. chinensis and C. keiskei. The previous studies also support this phylogenetic tree where similar results were obtained that showed weakly supported bootstrap value in some nodes of the Nolinoideae phylogeny [9][10][11][12][13][14][15]48]. The phylogenetic result also showed that Speirantha, Rohdea, Reineckea and Convallaria genus are constantly clustered in the same clade with a high-resolution value, even though high sequence divergence is noted in few protein-coding genes of these chloroplast genomes.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…So, in the present study, we constructed a maximum-likelihood phylogenetic tree based on concatenated 75 protein-coding genes of 19 Nolinoideae species and revealed that all the species formed a monophyletic group and S. gardenii formed a cluster with R. carnea, R. chinensis and C. keiskei. The previous studies also support this phylogenetic tree where similar results were obtained that showed weakly supported bootstrap value in some nodes of the Nolinoideae phylogeny [9][10][11][12][13][14][15]48]. The phylogenetic result also showed that Speirantha, Rohdea, Reineckea and Convallaria genus are constantly clustered in the same clade with a high-resolution value, even though high sequence divergence is noted in few protein-coding genes of these chloroplast genomes.…”
Section: Discussionsupporting
confidence: 81%
“…Until recently, only a few complete chloroplast genome sequences for this Nolinoideae subfamily have been deposited in GenBank, with the very first being that of Polygonatum cyrtonema in 2015. Owing to the development of high-throughput sequencing technologies, additional Nolinoideae chloroplast genomes were sequenced [9][10][11][12][13][14][15], but the genus Speirantha has to date remained unexplored. Therefore, in the present study, we sequenced the S. gardenii chloroplast genome and compared it with its closed related other Nolinoideae members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial gene annotation was done by Geneious R11 v11.0.5 (Biomatters Ltd, Auckland, New Zealand) based on the chloroplast genome of P. kingianum (MN934979; Jin et al. 2020 ). Genes that could not detected were further identified by Blastn ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ).…”
mentioning
confidence: 99%